Spatio-Temporal Parameters\' Changes in Gait of Male Elderly Subjects - Heydar Sadeghi; Hamid Reza Norouzi (Sālmand, 2010)
Objectives: The purpose of this study was to compare spatio-temporal gait parameters between elderly and young male subjects.